If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(r + -4) + -5(r + -7) = 4r + 6 + 6 + 1 Reorder the terms: -1(-4 + r) + -5(r + -7) = 4r + 6 + 6 + 1 (-4 * -1 + r * -1) + -5(r + -7) = 4r + 6 + 6 + 1 (4 + -1r) + -5(r + -7) = 4r + 6 + 6 + 1 Reorder the terms: 4 + -1r + -5(-7 + r) = 4r + 6 + 6 + 1 4 + -1r + (-7 * -5 + r * -5) = 4r + 6 + 6 + 1 4 + -1r + (35 + -5r) = 4r + 6 + 6 + 1 Reorder the terms: 4 + 35 + -1r + -5r = 4r + 6 + 6 + 1 Combine like terms: 4 + 35 = 39 39 + -1r + -5r = 4r + 6 + 6 + 1 Combine like terms: -1r + -5r = -6r 39 + -6r = 4r + 6 + 6 + 1 Reorder the terms: 39 + -6r = 6 + 6 + 1 + 4r Combine like terms: 6 + 6 = 12 39 + -6r = 12 + 1 + 4r Combine like terms: 12 + 1 = 13 39 + -6r = 13 + 4r Solving 39 + -6r = 13 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 39 + -6r + -4r = 13 + 4r + -4r Combine like terms: -6r + -4r = -10r 39 + -10r = 13 + 4r + -4r Combine like terms: 4r + -4r = 0 39 + -10r = 13 + 0 39 + -10r = 13 Add '-39' to each side of the equation. 39 + -39 + -10r = 13 + -39 Combine like terms: 39 + -39 = 0 0 + -10r = 13 + -39 -10r = 13 + -39 Combine like terms: 13 + -39 = -26 -10r = -26 Divide each side by '-10'. r = 2.6 Simplifying r = 2.6
| 4y+37=9 | | 3(2+u)-u=4+2(u+1) | | 4(x-2)=1 | | 2x-3(1)=5 | | 149=5/9(f-32) | | 14p+-3p=-11 | | 18(18-3x)=2(6-14x) | | 6+4(x+5)-x= | | 3n-5n+4+4n=36 | | 6b^2-12b-210=0 | | 120x=180(5-x) | | 2y+2=2y+1 | | x+4*2+2x= | | 3x(x+20)=60 | | 5(x+3)-(x-7)= | | -4(-14-19a)=7(11a+20)-a | | (6+w)(3w+7)=0 | | 3x+8y=9(y+2y+7) | | 13c+51c=-26 | | -11=x+8x+7 | | 5y+5=y(8-2y) | | 13(x-3)-22x=-18 | | v=3.14(3.14)(h) | | x+18+2x=-14-2x-18 | | X+(2x+0.10)=2.5 | | 2x+n=3 | | 95+52a=303 | | y=x^2-11x+20 | | 0.5x+0.4=0.08x-0.5 | | 5b+20=1.75 | | 6x-4=3x-28 | | 3x^2+23=4 |